Heterogeneous responses of temperate-zone amphibian populations to climate change complicates conservation planning. Issue 1 (December 2017) - Muths, E.; Chambert, T.; Schmidt, B.; Miller, D.; Hossack, B.; Joly, P.; Grolet, O.; Green, D.; Pilliod, D.; Cheylan, M.; Fisher, R.; McCaffery, R.; et al.
Abstract The pervasive and unabated nature of global amphibian declines suggests common demographic responses to a given driver, and quantification of major drivers and responses could inform broad-scale conservation actions. We explored the influence of climate on demographic parameters (i.e., changes in the probabilities of survival and recruitment) using 31 datasets from temperate zone amphibian populations (North America and Europe) with more than a decade of observations each. There was evidence for an influence of climate on population demographic rates, but the direction and magnitude of responses to climate drivers was highly variable among taxa and among populations within taxa. These results reveal that climate drivers interact with variation in life-history traits and population-specific attributes resulting in a diversity of responses. This heterogeneity complicates the identification of conservation 'rules of thumb' for these taxa, and supports the notion of local focus as the most effective approach to overcome global-scale conservation challenges.